Microstrip Antenna Gain Enhancement using Multilayer Substrate and Superstrate Structure for Space-Based ADS-B Surveillance - edwar EDWAR; Gilda Priscilla; Levy Olivia Nur; Putri Indra Wahyuningsih; Amanda Nurul Islam Ali (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2022)
Aircraft traffic monitoring is an important part in increasing flight security. Automatic Dependent Surveillance Broadcast (ADS-B) is used to run this task. The authority usually uses ground-based ADS-B signal receiver to monitor the aircraft traffic. However, this system is unable to detect the aircraft position when it is in a remote area. -based ADS-B can be the solution to this problem with the increase in the surveillance coverage by installing the ADS-B receiver system on a satellite platform such a . To enable this system, a high gain antenna is needed. This paper investigated a superstrate multilayer microstrip antenna as a candidate for this technology. The multilayer substrate and superstrate structure were combined with a microstrip antenna to achieve a high gain performance without increasing the antenna dimension significantly. The multilayer method produced 4.327 dBi of antenna gain and it was rising into 4.946 dBi after being integrated with the superstrate layer by a computer simulation. The fabricated antenna gain was 4.505 dBi which was still considerably high compared to the other previous works. This antenna was designed by following the CubeSat form factor standard so it can be installed into the spacecraft easily.